Smallholder groundwater irrigation in Sub-Saharan Africa: country-level estimates of development potential - Pavelic, Paul; Villholth, Karen G.; Shu, Yunqiao; Rebelo, Lisa-Maria; Smakhtin, V. (2023)
The abundance of groundwater resources of Sub-Saharan Africa is generally well recognized, but quantitative estimates of their potential for irrigation development are lacking. This study derives estimates using a simple and generic water balance approach and data from secondary sources for 13 countries. Even with conservative assumptions and accounting for water demands from other sectors, including the environment, a 120-fold increase (by 13.5 million hectares) in the area under groundwater irrigation is possible for the countries considered. This expansion could improve the livelihoods of approximately 40% of the present-day rural population.